(untitled) - Poonam S. Deshpande; Dupadahalli Kotresha; Rahmah Noordin; Muhammad Hafiznur Yunus; Geita Saadatnia; Majid Golkar; Sabariah Osman; Izzati Zahidah Abdul Karim; Fatemeh Ghaffarifar (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
Toxoplasmosis is an important cause of congenital infection. The present study was performed to evaluate the usefulness of recombinant (r) GRA-7 cloned from nucleotides (n) 39-711 in discriminating between acute and chronic toxoplasmosis. First, commercial IgM, IgG and IgG avidity ELISAs were used to determine the serological profile of the sera. Serum samples were from 20 symptomatic patients with acute infection (low IgG avidity, IgM positive), 10 with chronic infection (high IgG avidity, IgM negative) and 10 with indeterminate IgG avidity (IgM positive) which were tested for IgG avidity status with an in-house developed IgG avidity Western blot using the rGRA-7 recombinant antigen. All 20 sera from cases of probable acute infection showed bands which either faded out completely or reduced significantly in intensity after treatment with 8 M urea, whereas the band intensities of the 10 serum samples from chronic cases remained the same. Of the 10 sera with indeterminate IgG avidity status, after treatment with 8 M urea the band intensities with six sera remained the same, two sera had completely faded bands and another two sera had significantly reduced band intensities. Discrimination between acute and chronic toxoplasmosis was successfully performed by the in-house IgG avidity Western blot.